Effect of arum manis mango peel extract on cholesterol and triglyceride levels in dyslipidemic Sprague-Dawley rats - Saputra, Taufik; Naufal, Haidar Satya; Utomo, Astika Widy; Widyastiti, Nyoman Suci; Kurniawan, Muhammad Farhan; Azizah, Arfianty Nur (Medical Journal of Indonesia, 2023)
BACKGROUND Dyslipidemia is characterized by an increase in low-density lipoprotein (LDL) and triglyceride (TG) levels and a decrease in high-density lipoprotein (HDL). Cholestyramine as an antidyslipidemia has several side effects, so an alternative is needed. Pectin is a natural substance with a mechanism of action similar to that of cholestyramine. Mango peel is one of the sources of pectin, containing 10–15% of this substance. This study aimed to prove the effect of arum manis mango (Mangifera indica L.) peel extract on LDL, HDL, and TG levels in dyslipidemic Sprague-Dawley rats. METHODS 25 Sprague-Dawley rats were divided into 5 groups. All groups were given high-fat diet for the first 18 days, followed by standard feed (negative control group), cholestyramine (Sequest®) 80 mg/200 g body weight (standard treatment group), and mango peel extract (M-90 [90 mg/day], M-180 [180 mg/day], and M-360 [360 mg/day] groups) for the next 15 days. LDL and HDL levels were analyzed using the cholesterol oxidase-phenyl aminopyrazolone method and TG level using the glycerol-3-phosphate-oxidase-phenol-aminophenazone method. RESULTS The M-360 group reduced the LDL level (p = 0.015), while the standard treatment group increased the HDL level (p = 0.042). Although significant TG level changes were found in the negative control, standard treatment, and M-360 groups (p = 0.042), the mean differences of LDL, HDL, and TG levels between groups were not significantly different (p = 0.245, 0.328, and 0.454, respectively). CONCLUSIONS M. indica peel extract reduced LDL and TG levels at 360 mg/day.